The colonial politics of global health : France and the United Nations in postwar Africa - Pearson, Jessica Lynne, 1984- (Harvard University Press, 2018)
In The Colonial Politics of Global Health, Jessica Lynne Pearson explores the collision between imperial and international visions of health and development in French Africa as decolonization movements gained strength. After World War II, French officials viewed health improvements as a way to forge a more equitable union between France and its overseas territories. Through new hospitals, better medicines, and improved public health, French subjects could reimagine themselves as French citizens. The politics of health also proved vital to the United Nations, however, and conflicts arose when French officials perceived international development programs sponsored by the UN as a threat to their colonial authority. French diplomats also feared that anticolonial delegations to the United Nations would use shortcomings in health, education, and social development to expose the broader structures of colonial inequality. In the face of mounting criticism, they did what they could to keep UN agencies and international health personnel out of Africa, limiting the access Africans had to global health programs. French personnel marginalized their African colleagues as they mapped out the continent's sanitary future and negotiated the new rights and responsibilities of French citizenship. The health disparities that resulted offered compelling evidence that the imperial system of governance should come to an end. Pearson's work links health and medicine to postwar debates over sovereignty, empire, and human rights in the developing world. The consequences of putting politics above public health continue to play out in constraints placed on international health organizations half a century later.--